Application of a hybrid biofilter column for the removal of Cr(VI) from aqueous solution using an indigenous bacterial strain Pseudomonas taiwanensis. Issue 1 (2nd January 2016) - Majumder, Subhajit; Raghuvanshi, Smita; Gupta, Suresh
ABSTRACT: In the present study, a laboratory-scale biofilter column was designed and fabricated. It was packed with a mixture of coal and compost as a packing medium. The column was enriched with an indigenous bacterial strain Pseudomonas taiwanensis isolated from aerobic mixed culture of Sewage Treatment Plant, BITS-Pilani, Pilani campus. The removal of hexavalent chromium [Cr(VI)] from aqueous solution was investigated in the biofilter column. The entire biofiltration operation was divided into five phases (I to V) for a period of 63 days. Biofilter column was subjected to shock loading conditions for 20 days immediately after 63 days of operation. The maximum removal efficiency of 89.4% was obtained during phase V for Cr(VI) inlet concentration of 40 mg L −1 . During shock loading, maximum removal efficiency was obtained as 90% for 48.5–50 mg L −1 of initial Cr(VI) concentration. Kinetic parameters of biofiltration process for Cr(VI) removal were also determined by fitting Michaelis-Menten kinetic model with experimental data. The Michaelis-Menten kinetic constants were obtained as 0.258 mg L −1 min −1 and 26.83 mg L −1 . It was found that Ottengraf-Van den Oever model with zero-order diffusion limitation fit the experimental data quite well for phases III, IV, and V with coefficient of determination ( R 2 ) values .97, .99, and .984, respectively. A possible method for safe disposal of packing medium was also presented in this study.